Pemanfaatan Media Kartu Bergambar Guna Mengenali Diri Berdasarkan Gender pada Siswa Playgroup - Fifit Safitri; Daroe Iswatiningsih; Uun Hasunah (Al Fitrah: Journal Of Early Childhood Islamic Education, 2026)
Self-identity recognition is a fundamental aspect of young children’s social and emotional development. One important component of self-identity is gender recognition, which serves as the basis for children to understand roles and distinctions between males and females. This study aims to describe the use of picture card media as a learning aid to support playgroup students in identifying their gender-based self-identity. This research employed a qualitative descriptive approach, with data collected through classroom observations, documentation of instructional media, and teacher reflections on children’s learning processes. The findings indicate that picture cards effectively enhance children’s understanding of gender differences. Clear and observable visuals help children associate physical characteristics and social roles with each gender. Following the activity, 75 % of the students were able to state their own gender and differentiate characteristics of males and females. Overall, picture card media proved to support gender identity learning in an enjoyable, interactive manner suited to early childhood developmental stages. These findings offer practical implications for early childhood educators to design engaging visual media aligned with children’s concrete thinking, as well as theoretical implications that reinforce experiential learning approaches in early childhood education.